(untitled) (Economic and Political Thought, 2015)
As the title suggests, the article aims to show the significance of Poland’s accession to the European Union for the Polish domestic and foreign policy from the perspective of its 11-year membership. However, it does not only aim to assess Poland’s membership so far but, first of all, show new threats to the EU and – from this perspective – new challenges and tasks for the integration policy of Poland. The main thesis of the article is a statement that Poland’s accession to the EU was, and still is, one of the most important events in the modern history of Poland. It became a turning point in the Polish domestic and foreign policy. Thanks to the accession to the EU, Poland has strengthened its position in Europe and the world. However, it must work out a new strategy today and determine further objectives for our activities in the EU, which should be adequate to the quickly changing international reality.